Students' Perceptions of Drug Abuse and its Implications in Guidance and Counseling - Rahmi Dani; Yarmis Syukur (Universitas Negeri Padang, 2019)
This research is motivated by the fact that there are still students who do not know the adverse effects of drugs, there are still students who say good drugs, there are students who approach the characteristics of drug abuse seen from the physical, some students still smoke both in the school environment and the surrounding environment, still some are bored because it is not interesting to listen to information on drug abuse, and the provision of counseling services by BK teachers about drugs is still lacking by students. This study aims to describe students' perceptions of drug abuse and its implications in BK services. This research is a type of descriptive research using quantitative methods. The population of this study was students of class XI and XII of SMA Negeri 1 Batipuh, Tanah Datar District, totaling 515 people. A total of 225 people were selected using the Proportional Random Sampling technique. The instrument used was a questionnaire for students' perceptions of drug abuse using a Likert scale. Data were analyzed using descriptive statistical techniques. General research findings show that students' perceptions of drug abuse are good (78.67%). Based on the aspect of cognition in the good category (78.22%), students' perceptions based on the affection aspect were in the good category (47.11%) and perceptions based on the konasi aspect were in the good category (77.33%). Based on the research findings, it is suggested to the school counselor / school counselor to be able to provide guidance and counseling services in the form of information services, and group guidance services so that students are able to have good perceptions and increase students' insight on drug abuse.